How Social Values Affect Welfare Attitudes? A Cross-National Comparison - Lee, Eun Kyung (Advances in Social Sciences Research Journal, 2023)
This preliminary study examines how social values explain the cross-national differences in welfare attitudes, grounded in Inglehart and Baker’s (2000) social value theory. By employing secondary data collected by World Values Survey [WVS], this preliminary study empirically tested two hypotheses: (H1) Nations that emphasize the secular-rational values have more pro-welfare attitudes than the nations encouraging the traditional values; and (H2) Nations that promote the values of self-expression have more pro-welfare attitudes than nations that foster survival values. Results of the study demonstrated social values significantly affects public’s welfare attitude, controlling economic and ideological factors. People in societies which promote the value of self-expression, such as respect for diversity and political participation, are more likely to support more expansive social welfare policies.